Description of the tadpoles of two endemic frogs: the Phu Luang cascade frog Odorrana aureola (Anura: Ranidae) and the Isan big-headed frog Limnonectes isanensis (Anura: Dicroglossidae) from northeastern Thailand - Ampai, Natee; Rujirawan, Attapol; Arkajag, Jirachai; Mcleod, David S.; Aowphol, Anchalee (Zootaxa, 2015)
We describe the external morphology of the tadpoles of two frogs endemic to Thailand: the Phu Luang cascade frog    (Odorrana aureola) and the Isan big-headed frog (Limnonectes isanensis) from the type localities in the Phu Luang Wildlife Sanctuary, Loei Province, northeastern Thailand. Morphological and genetic characters (16S rRNA) were used to identify specimen and match tadpoles to the adults. Detailed descriptions of external morphology and coloration in life are provided for both species. We provide a brief discussion of the ecology of these tadpoles and a comparison to previously published data from tadpoles of closely related taxa. Additionally, we provide evidence for the utility of larval morphology in resolving the taxonomic puzzles presented by cryptic species complexes.